KEPADATAN LEKSIKAL PARAGRAF SKRIPSI BERBAHASA INGGRIS: ANALISIS UNSUR QUALIFIER - A. Djawad Mubasyir (Fakultas Sastra Universitas Negeri Malang, 2014)
This study compared the lexical density of undergraduate theses in the English Department of Universitas Negeri Jakarta with that of the articles published in certain reputable international journals. The approach used was the Systemic Functional Linguistics (SFL). The result of the comparison shows that the paragraphs in the undergraduate theses have lower average of lexical density than those in the journal articles.